2002
DOI: 10.1046/j.0960-7692.2001.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of transvaginal three‐dimensional endometrial volume measurements with virtual organ computer‐aided analysis (VOCAL) during ovarian stimulation

Abstract: VOCAL provides a reproducible method for the estimation of the endometrial volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 12 publications
1
45
0
4
Order By: Relevance
“…[19][20][21] According to our preliminary results, the rotation plane and angle do not significantly affect the reproducibility of In this study, we have evaluated the reproducibility of the measurements of ovarian volume, number of antral follicles, and power Doppler indices with the VOCAL imaging program. Groups in 2 functional stages have been assessed: a group of women examined after long pituitary suppression with a GnRH analogue and a second group analyzed after the ovarian stimulation with recombinant FSH.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] According to our preliminary results, the rotation plane and angle do not significantly affect the reproducibility of In this study, we have evaluated the reproducibility of the measurements of ovarian volume, number of antral follicles, and power Doppler indices with the VOCAL imaging program. Groups in 2 functional stages have been assessed: a group of women examined after long pituitary suppression with a GnRH analogue and a second group analyzed after the ovarian stimulation with recombinant FSH.…”
Section: Discussionmentioning
confidence: 99%
“…These options were chosen for the reason that A plane is the habitual one in the ovary visualization and it was previously demonstrated that there are no significant statistical differences in reproducibility among A and C plane in the endometrium study. 11,12 Also in the ovary, the reproducibility with this characteristics was proved. 13 Three-dimensional power Doppler indices were calculated using histogram facility.…”
Section: Methodsmentioning
confidence: 99%
“…VPB volumes were stored and analyzed off-line using Virtual Organ Computer-Aided analysis (VOCAL) [14][15][16][17][18] program integrated in the Voluson 730E and 4D view program. The conditions were standardized as follows: multiplanar mode and establishment of the work image in plane A, with the virtual axis of reference lying between the basal plate and the chorionic plate.…”
Section: Methodsmentioning
confidence: 99%